The anti-inflammatory and anti-apoptotic effects of Achillea millefolium L. extracts on Clostridioides difficile ribotype 001 in human intestinal epithelial cells - Hamideh Raeisi; Masoumeh Azimirad; Samaneh Asadi-Sanam; Hamid Asadzadeh Aghdaei; Abbas Yadegar; Mohammad Reza Zali (BMC, 2024)
Abstract Background Clostridioides difficile infection (CDI) is one of the most common health care-acquired infections. The dramatic increase in antimicrobial resistance of C. difficile isolates has led to growing demand to seek new alternative medicines against CDI. Achillea millefolium L. extracts exhibit strong biological activity to be considered as potential therapeutic agents. In this work, the inhibitory effects of A. millefolium, its decoction (DEC) and ethanol (ETOH) extracts, were investigated on the growth of C. difficile RT001 and its toxigenic cell-free supernatant (Tox-S) induced inflammation and apoptosis. Methods Phytochemical analysis of extracts was performed by HPLC and GC analysis. The antimicrobial properties of extracts were evaluated against C. difficile RT001. Cell viability and cytotoxicity of Caco-2 and Vero cells treated with various concentrations of extracts and Tox-S were examined by MTT assay and microscopy, respectively. Anti-inflammatory and anti-apoptotic effects of extracts were assessed in Tox-S stimulated Caco-2 cells by RT-qPCR. Results Analysis of the phytochemical profile of extracts revealed that the main component identified in both extracts was chlorogenic acid. Both extracts displayed significant antimicrobial activity against C. difficile RT001. Moreover, both extracts at concentration 50 µg/mL had no significant effect on cell viability compared to untreated cells. Pre-treatment of cells with extracts (50 µg/mL) significantly reduced the percentage of Vero cells rounding induced by Tox-S. Also, both pre-treatment and co-treatment of Tox-S stimulated Caco-2 cells with extracts significantly downregulated the gene expression level of IL-8, IL-1β, TNF-α, TGF-β, iNOS, Bax, caspase-9 and caspase-3 and upregulated the expression level of Bcl-2. Conclusion The results of the present study for the first time demonstrate the antimicrobial activity and protective effects of A. millefolium extracts on inflammatory response and apoptosis induced by Tox-S from C. difficile RT001 clinical strain in vitro. Further research is needed to evaluate the potential application of A. millefolium extracts as supplementary medicine for CDI prevention and treatment in clinical setting.